Nutrition in the patient with chronic obstructive pulmonary disease (COPD) - Ojeda-Ibáñez, María Fe (2022)
Chronic obstructive pulmonary disease (COPD) is a serious public health problem worldwide, whose statistics have unfortunately been increasing, aiming to be the third leading cause of death in 2030 Nutrition in the patient with chronic obstructive pulmonary disease is a determining factor in the prognosis of this type of patients, so an adequate, comprehensive and timely evaluation should be carried out for all patients with this diagnosis a low carbohydrate, and a high fat dietary regimen should be prescribed. There is evidence that the use of nutritional supplements would improve quality of life in COPD patients.